AS BASES TEÓRICO-METODOLÓGICAS DOS CURRÍCULOS DE GEOGRAFIA PARA OS ANOS FINAIS DO ENSINO FUNDAMENTAL NO PARANÁ - Barbosa, Valdivânia Pereira (2018)
Beginning in the mid-1980s, public education agents from Paraná developed and implemented curricular guidelines for the state school network. Curricular guidelines come not only from official bodies, but from other segments of society. The historical context, class interests and transformations in scientific, philosophical and geographic thought are determinant in the elaboration of curricular propositions. The research, in an approach with historical and dialectical materialism, had as objective to evaluate the socio-historical determinants and the theoretical-methodological bases contained in the curricular proposals of Geography for the Final Years of Elementary Education, from the state network of Paraná, from 1990 to 2017. We seek to identify the context of transformations in education and geography, as well as the insertion of this science in school curricula. The research was conducted based on the theoretical and methodological assumptions of the bibliographical and documentary research and covered the Basic Curriculum for the Public School of Paraná, the National Curricular Parameters, the Basic Curricular Guidelines for Basic Education and the Study Plan of the Itinerant Schools of the Movement Landless Rural Workers. In each curricular proposal we analyze the object of study of Geography and the concepts that contribute to explain it, the teaching objectives, the teaching methodologies, the conception / function of the evaluation of the learning. The four documents present coherence and internal contradictions. The four proposals admit that the object of study of Geography is the geographic space. Only the Basic Curriculum does not explicitly state the concepts / categories of Geography. Starting from the National Curricular Parameters, the proposal of the use of the concepts of Geography in school education. This proposal also presented, at the time, a new approach to the teaching of cartography. In the Basic Curriculum, in the National Curriculum Parameters and in the Curriculum Directives of Basic Education, the objectives of the teaching of Geography are coherent with the theoretical-methodological assumptions. The MST Study Plan, in addition to teaching objectives, proposes human, omnilateral training as a fundamental principle of education. The contents selected are consistent with the objectives of each analyzed proposal of Geography. Historical and dialectical materialism is the methodological approach in the Basic Curriculum and in the MST Study Plan; the National Curricular Parameters present an eclectic approach with emphasis on phenomenology; in the Basic Education Guidelines are critical approaches. Each document that succeeds the previous one keeps aspects of the remote, presents new approaches of Geography, and surpasses in some propositions.